2008
DOI: 10.1038/mp.2008.39
|View full text |Cite
|
Sign up to set email alerts
|

Tph2 gene variants modulate response control processes in adult ADHD patients and healthy individuals

Abstract: Although therapeutic interventions in attention-deficit/hyperactivity disorder (ADHD) still focus on the dopaminergic system, recent studies indicate a serotonergic dysfunction in this disease as well. In that respect, several variants of the tryptophan hydroxylase gene (TPH2), which codes for the rate-limiting enzyme in the biosynthesis of serotonin (5-HT), have been associated with ADHD. The rs4570625 G-allele polymorphisms of the TPH2 gene have already been related to altered reactivity of the brain during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 34 publications
3
54
0
Order By: Relevance
“…It also replicates previous reports of altered ERP measures of prefrontal response control in children suffering from ADHD (Fallgatter et al, 2004) and a diminished NGA in adults with a suspected ADHD during childhood (Fallgatter et al, 2005). In the latter study, the diminished NGA was mainly caused by a more anterior centroid in the Go condition (Fallgatter et al, 2005); this is also in line with our results, as patients showed a significantly more anterior location of the Go centroid as compared with that in the control group (see also Baehne et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It also replicates previous reports of altered ERP measures of prefrontal response control in children suffering from ADHD (Fallgatter et al, 2004) and a diminished NGA in adults with a suspected ADHD during childhood (Fallgatter et al, 2005). In the latter study, the diminished NGA was mainly caused by a more anterior centroid in the Go condition (Fallgatter et al, 2005); this is also in line with our results, as patients showed a significantly more anterior location of the Go centroid as compared with that in the control group (see also Baehne et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…In schizophrenic patients the NGA was found to be related to variants of the catechol-O-methyltransferase (COMT) gene (Ehlis et al, 2007). Furthermore, in one of our previous publications, the tryptophan hydroxylase (TPH2) gene was found to have a significant effect on the NGA in adult ADHD patients (Baehne et al, 2009). In this study, we hypothesized that the SLC6A3 genotype would significantly affect the NGA, particularly in ADHD patients.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This agrees with our behavioral findings showing similar persistence of elevated scores on multiple CBCL scales, and of higher interview-derived inattention and hyperactivity/ impulsivity scores for the ADHD compared to the control group of this sample (4), even though earlier work had suggested a more prominent remission of behavioral impulsivity than of inattention scores (52). The findings also confirm that the cued CPT contains a well validated Go-NoGo task (53,54,55,56), and that a lower probability of the NoGo condition is not critical for typical anterior NoGo P300 topographies (57,58). Still, the inhibitory load on NoGo trials of this cued CPT is somewhat lower than in typical GoNoGo tasks, where Go probabilities of about 70% also require suppressing habitual, high probability responses.…”
Section: Discussionsupporting
confidence: 82%
“…Indicators of response inhibition have also thought to be associated with the variation in noradrenaline and dopamine signaling systems, but specifics of these associations are somewhat different, pointing, in particular, to the variation in the DRD4 and DAT1/SLC6A3 (Congdon et al 2008) and COMT (Congdon et al 2009) genes. Although serotonin neuromodulation does not appear to be pivotal to response inhibition, there are studies connecting variation in this facet of EF and variation in the genes involved in the turnover of serotonin in the corresponding brain circuits, e.g., the variation in the TPH2 gene (Baehne et al 2009). …”
Section: Involved In Critical-analytic Thinkingmentioning
confidence: 99%